1968
DOI: 10.1099/00221287-54-2-169
|View full text |Cite
|
Sign up to set email alerts
|

The Aerosol Survival and Cause of Death of Escherichia coli K12

Abstract: SUMMARYThe survival of Escherichia coli K 1 2 HfrC sprayed from distilled water into a nitrogen atmosphere as a function of aerosol age and of storage relative humidity (RH) is demonstrated. The survival pattern was typically that of E. coli, i.e. marked instability in a region at high RH and better stability at low RH. The results of changing the RH from the storage RH to IOO % or 30 % are described. Comparison of survival in nitrogen with that in air showed air to be slightly toxic, the toxic component being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1

Year Published

1969
1969
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 11 publications
4
26
1
Order By: Relevance
“…Throughout these investigations differences seemed to exist between the behaviour of the two strains of Escherichia coli used and that of E. coli K 12 as reported by Cox (1968). Both of the strains used here were stable at relative humidities above 80%, which contrasted with the behaviour of the E. coli K I~ strain used by Cox, which apparently is unstable in aerosols at high RH values.…”
Section: Influence Of Nz Puritycontrasting
confidence: 46%
See 2 more Smart Citations
“…Throughout these investigations differences seemed to exist between the behaviour of the two strains of Escherichia coli used and that of E. coli K 12 as reported by Cox (1968). Both of the strains used here were stable at relative humidities above 80%, which contrasted with the behaviour of the E. coli K I~ strain used by Cox, which apparently is unstable in aerosols at high RH values.…”
Section: Influence Of Nz Puritycontrasting
confidence: 46%
“…Most investigators have found organisms held at 25" and at relative humidities above 75% to be stable. In contrast, however, Cox (1967Cox ( ,1968 found that Escherichia coli died rapidly when held in an atmosphere of nitrogen at relative humidities between 85 and 75%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, if species A.izH,O does exist in bacteria, it would exist in an environment which contains much weakly bound water. Such an environment would occur in the interspace between the cytoplasn~ic membrane and the cell wall and this possibility is consistent with data obtained from entirely different experiments, which suggested that cell wall synthesis and (or) cell division are probably inhibited through the toxic action of oxygen (6,9,11). Furthermore, the relationship between 1 and a, explains the apparent lack of a toxic action of oxygen at high RH, because reaction rate depends upon concentration, and provided that the concentration (moles per liter) is very small, then the rate of reaction will also be very small.…”
Section: Resultssupporting
confidence: 82%
“…While it has been generally accepted that soil can serve as an intermediate home for pathogens before they transfer to their hosts, it is not clear where and how the microbes in the soil transfer from their original habitats to the atmosphere2122232425. Considering that most microbes prefer aqueous environments to survive, it is still a mystery to explain how viable soil-based microbes spread much further and faster than would be expected through the air12627. Futhermore, even though we know that after a rainfall there is a rapid increase of bioaerosol concentration in the air, we have not explained the wide spread of microbes with the transfer modes discovered to date92829.…”
mentioning
confidence: 99%